SIMULASI MOTOR DC BLM57050 ORDE 2 DENGAN ZIEGLER-NICHOLS - Purwidi asri; Anggara Trisna Nugraha; Rama Arya Sobhita, (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2025)
DC motors are widely used in various industrial applications and automatic control systems due to their ability to provide high torque and good dynamic response. This research focuses on the mathematical modeling and simulation of a DC motor type BLM57050 using a second-order approach. The mathematical model considers key parameters such as resistance (R), inductance (L), torque constant (Kt), and moment of inertia (J). This model is used to simulate the system's response in both open loop and closed loop configurations. In the open loop configuration, the motor's response to input voltage is analyzed without feedback mechanisms, identifying initial dynamic characteristics such as rise time, settling time, and delay time. This study provides comprehensive insights into the dynamic characteristics of the BLM57050 DC motor and emphasizes the importance of implementing PID controllers to achieve optimal system performance. Simulations were conducted using MATLAB/Simulink software, allowing clear visualization of the system's response under various operating conditions. The results are expected to serve as a valuable reference for engineers and researchers in developing more efficient control systems for DC motor applications.